2009
DOI: 10.1159/000192792
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Speaking Rate onConsonant Vowel Coarticulation

Abstract: In 2007 Lindblom et al. introduced a methodological tool to disentangle consonant-vowel (CV) coarticulation attributable to emphatic stress apart from the vowel expansion effects known to accompany the prosodic overlay. After empirically accounting for the altered vowel positions, they reported small but consistent increases in F2 transition onsets in emphatically produced CVs that could not be attributed to vowel context influences, and that differed across stop place. At issue is whether the findings of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 26 publications
4
36
0
Order By: Relevance
“…Increasing or decreasing the rate at which speech is produced-which talkers do frequently in normal discourse for a variety of linguistic and paralinguistic reasons-has complex articulatory (and therefore acoustic) consequences in addition to the manifest effect of decreasing or increasing overall utterance duration. Increases in speech rate typically involve, among other things: (1) increased co-articulation, reduction, and assimilation (Gay 1981;Agwuele et al 2008); (2) reductions in segment duration that are dependent on stress placement and phoneme class (Lehiste 1970;Byrd and Tan 1996); and (3) increases in articulator 2 There is no distinction between reversed and constant amplitude when the competitor rate is set to zero. Hence, the data for C2 served as the zero-rate case for both amplitude-contour conditions in the two-factor ANOVA.…”
Section: Acoustic Consequences Of Changes In Speech Ratementioning
confidence: 99%
“…Increasing or decreasing the rate at which speech is produced-which talkers do frequently in normal discourse for a variety of linguistic and paralinguistic reasons-has complex articulatory (and therefore acoustic) consequences in addition to the manifest effect of decreasing or increasing overall utterance duration. Increases in speech rate typically involve, among other things: (1) increased co-articulation, reduction, and assimilation (Gay 1981;Agwuele et al 2008); (2) reductions in segment duration that are dependent on stress placement and phoneme class (Lehiste 1970;Byrd and Tan 1996); and (3) increases in articulator 2 There is no distinction between reversed and constant amplitude when the competitor rate is set to zero. Hence, the data for C2 served as the zero-rate case for both amplitude-contour conditions in the two-factor ANOVA.…”
Section: Acoustic Consequences Of Changes In Speech Ratementioning
confidence: 99%
“…Despite the preceding discussion, which suggests that acoustic effects of rate change may be small (relative to kinematic variability), studies of the acoustic effects of speaking rate change have identified a variety of speaker and context-related effects on formants (Agwuele, Sussman, & Lindblom, 2008;Fourakis, 1991;Gay, 1968Gay, , 1978Hertrich & Ackermann, 1995;Lindblom, 1963;Pitermann, 2000;Rosen et al, 2011;Tjaden & Weismer, 1998;van Son & Pols, 1992;Weismer & Berry, 2003). Taken together, these studies indicate a wide range of possible speaker-specific and context-related effects of speaking rate change.…”
Section: Acoustic Effects Of Speaking Rate Changementioning
confidence: 81%
“…In total there were 270 tokens analyzed per speaker in the rate study. Further details about the specific stimuli and conditions can be found in Lindblom et al [2007] and Agwuele et al [2008].…”
Section: Speech Samplesmentioning
confidence: 99%
“…Specifics of this methodology have been provided in detail in both Lindblom et al [2007] and Agwuele et al [2008], but will be briefly summarized below. Following this, a new figure, displaying both emphasis and rate data in the same plot, will be presented.…”
Section: Multiple Regression Analysesmentioning
confidence: 99%
See 1 more Smart Citation